Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Poor pulmonary health in Barataria Bay dolphins in the eight years following the Deepwater Horizon oil spill - Cynthia R. Smith; Teresa K. Rowles; Forrest M. Gomez; Marina Ivančić; Kathleen M. Colegrove; Ryan Takeshita; Forrest I. Townsend; Eric S. Zolman; Jeanine S. Morey; Veronica Cendejas; Jennifer M. Meegan; Whitney Musser; et al. (Frontiers in Marine Science, 2022)
The Deepwater Horizon (DWH) disaster resulted in large-scale contamination of bays, sounds, and estuaries in the northern Gulf of Mexico, home to multiple stocks of common bottlenose dolphins (Tursiops truncatus). Inhalation, aspiration, ingestion, and dermal absorption of oil and its toxic components were all considered possible routes of exposure for dolphins living within the oil spill footprint. To determine if dolphins were adversely impacted, catch-and-release health assessments were performed in heavily-oiled Barataria Bay (BB), Louisiana, and in Sarasota Bay (SB), Florida, a comparison site with no DWH oil contamination. Initial studies were conducted as part of a Natural Resource Damage Assessment (2011-2014) and follow-on studies were performed between 2016-2018 with support from the Gulf of Mexico Research Initiative. Ultrasound was used to evaluate the dolphins’ pulmonary health, including the presence/absence of pleural effusion, nodules, masses, consolidation, and alveolar interstitial syndrome (AIS). When present, AIS was further graded by severity (mild, moderate, or severe) and distribution. Based on the presence and severity of abnormalities, each dolphin was given an overall lung disease score (normal, mild, moderate, or severe). Normal to mild scores were considered within expected limits for a wild population, therefore the prevalence of normal-mild versus moderate-severe scores was compared between the oiled and unoiled sites. Separate analyses were conducted for dolphins alive in 2010 (and in BB, presumably exposed to DWH oil), and those born after 2010. For the dolphins alive in 2010, temporal trends were also examined using generalized additive models (GAMs). Results showed a strong difference (p=0.000357) in moderate to severe lung disease between the two sites for dolphins alive in 2010, but no significant difference (p=0.6745) between the sites for dolphins born after 2010. In BB dolphins, the prevalence of moderate to severe lung disease did not decrease in the years after the spill, and in fact, potentially worsened (p=0.0644 for trend over years), with the highest prevalence (0.61) being in 2018. Moderate to severe AIS remained a persistent finding in BB dolphins, and several animals had a pattern of AIS that was more severe ventrally than dorsally, with evidence of chronic, progressive disease states.

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Advances in cetacean telemetry: A review of single‐pin transmitter attachment techniques on small cetaceans and development of a new satellite‐linked transmitter design - Brian C. Balmer; Randall S. Wells; Laurens E. Howle; Aaron A. Barleycorn; William A. McLellan; D. Ann Pabst; Teri K. Rowles; Lori H. Schwacke; Forrest I. Townsend; Andrew J. Westgate; Eric S. Zolman (Marine Mammal Science, 2014)
Electronic tags have proven to be valuable tools in assessing small cetacean movement and behavior. However, problems associated with tag size and attachment have limited duration and damaged dorsal fins. These outcomes have motivated researchers to develop a new satellite‐linked tag design that reduces detrimental effects to tagged animals, while increasing transmission durations. The goals of this study were to review previous studies that deployed single‐pin transmitters and determine factors that influence transmission duration. Then, test these factors utilizing computational fluid dynamics ( CFD ) models to identify an optimal single‐pin satellite‐linked tag design, and evaluate this prototype through field studies. A review of four projects, which deployed 77 single‐pin radio tags, determined that tags attached along the lower third of the dorsal fin and approximately 33 mm from the trailing edge resulted in longer transmission durations and reduced negative impacts to the dorsal fin. Based upon these results and CFD modeling, prototype, single‐pin satellite‐linked tags ( n = 25) transmitted for 163 ± 22 d (mean ± 95% CI ) which greatly exceeded transmissions for previous small cetacean telemetry studies. These results suggest that the newly developed single‐pin satellite‐linked tag design strikes a balance between reducing impacts to the individual while maximizing transmissions.

Evaluating postintervention survival of free‐ranging odontocete cetaceans - Randall S. Wells; Deborah A. Fauquier; Frances M. D. Gulland; Forrest I. Townsend; Robert A. DiGiovanni (Marine Mammal Science, 2013)
Until recently, few data were available for evaluating postintervention survival of free‐ranging cetaceans receiving aid from humans through: rescue from stranding, with rehabilitation and release; rescue, rehabilitation and release of debilitated or entangled individuals that had not beached; rescue of entangled animals with immediate release; and rescue, transport, and release of out‐of‐habitat animals. Advances in medical diagnosis, husbandry and therapy have improved survival of rehabilitation cases, and advances in radio‐telemetry have improved postrelease monitoring. In total, 69 cases (1986–2010) were evaluated, involving 10 species of odontocete cetaceans with release data. Findings suggested a success criterion of surviving at least six weeks postrelease is useful in evaluating intervention strategies. No species had better success than others. Stranded beached cetaceans were less successful than free‐swimming rescued animals. Rehabilitated animals were less successful than those released without rehabilitation. Mass stranded dolphins fared better than single stranded animals. Old age, diminished hearing ability, and lack of maternal care were factors in several unsuccessful cases. Success is not clearly related to rehabilitation duration. Retaining healthy individuals from mass strandings until all animals are ready for release may reduce success for some. Transport durations for unsuccessful cases were greater than for successful cases.